A Novel Method to Measure the Powder Consumption of Dental Air-Polishing Devices - Marcel Donnet; Maxime Fournier; Patrick R. Schmidlin; Adrian Lussi (Applied Sciences, 2021)
Background: Oral preventive measures should be efficient, minimally invasive, and painless. Air-polishing has this potential. As the efficiency and abrasivity of powders are dependent on the amount of powder projected, a better understanding of this characteristic will help us to determine the most effective and least invasive device. Method: A new laboratory set-up was designed using light diffusion to measure powder consumption with high accuracy due to its high sampling rate, even at short time intervals (<1 s). We tested six different marketed air-polishers of two different working types: Table-top and Handy. Results: All of the devices presented some powder delivery fluctuations. These differences were manufacturer-dependent. The powder delivery stability varied by up to two times, and ranged among the Table-top devices in the following order: E1 < M2 < N2. The mean powder consumption also varied by up to 2.9 times, in the following order: E1 < N2 < M3. All of the Handy devices presented a short treatment time and poor flow regularity, and consumed significantly more powder than the Table-top devices (by approximately +25%). Conclusion: The powder consumption analysis showed distinct differences between the devices. Therefore, the clinical results among the devices cannot be compared, as their working mechanisms are very different.